In vitro probiotic properties of selected lactobacilli and multi-strain consortium on immune function, gut barrier strengthening and gut hormone secretion. (June 2019) - Belguesmia, Yanath; Alard, Jeanne; Mendil, Rezak; Ravallec, Rozenn; Grangette, Corinne; Drider, Djamel; Cudennec, Benoit
Graphical abstract: Highlights: Three Lactobacillus strains from vaginal flora were studied for their probiotic traits. The strain 395 and the 3RG consortium exhibit anti-inflammatory effect on PBMC model. L. gasseri ICVB392 and the 3RG consortium strengthen Caco-2 epithelial barrier. The lactobacilli strains are able to modulate the secretion of CCK and GLP-1 hormones. Specific antagonist/inhibitor impact differentially the secretion of these hormones. Abstract: Lactobacillus reuteri ICVB395, L. gasseri ICVB392 and L. gasseri ICVB396 strains, isolated from vaginal microbiota, were investigated for their probiotic traits. L. reuteri ICVB395 strain and the 3RG consortium, associating these three Lactobacillus strains, showed the best anti-inflammatory profile on peripheral blood mononuclear cell (PBMC) while L. gasseri ICVB392 was the most potent together with the 3RG consortium to strengthen a Caco-2-derived epithelial barrier. The three studied strains induced various secretion levels of glucagon-like peptide 1 (GLP-1) and cholecystokinin (CCK) by STC-1 enteroendocrine cells, whereas the 3RG consortium was globally less performing. Specific antagonists of protein G receptors, CaSR (Calcium-Sensing Receptor) and GPRC6A (G protein-coupled receptor family C group 6 member A), and inhibitor of the peptide transporter Pept-1 provoked differential modulation of the GLP-1 and CCK secretion by STC-1 cells, indicating that different mechanisms are involved in the capacity of lactobacilli and the 3RG to modulate gut hormones secretion.